Boom, bust, recovery – What next in private capital flows to emerging markets? - Peter Nunnenkamp (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2000)
International capital markets are far from functioning perfectly. During the last decade, they overshot both ways: The earlier boom of private capital flows to emerging market economies (EMEs) turned out to be the prelude to the drama of seriously impaired access to foreign capital in the late 1990s. Current concerns are that the next boomand- bust cycle is in the making, after EMEs have been surprisingly quick in returning to international capital markets. Capital market failures notwithstanding, it is hypocritical to blame foreign investors for having caused financial crises. Recent crisis episodes do not support the view that pure contagion has affected EMEs with prudent macroeconomic policies and sound financial sectors. Economic fundamentals do matter still. However, increased international capital mobility implies that foreign (and domestic!) investors react more quickly and drastically to any news, be it bad or good news. Domestic policy failures underlying recent financial crises differed considerably. Brazil experienced a conventional currency crisis, caused by inconsistent macroeconomic policies. Korea was characterized by structural weaknesses such as a highly leveraged corporate sector and fragile financial institutions, and by a policy-induced composition of external financing that rendered the country extremely vulnerable to changing expectations of foreign investors. A differentiated analysis of international capital markets is required in order to assess the role of private foreign capital in financing EMEs on a sustainable basis. The reaction to financial crises differed between major types of foreign investors. Notably foreign direct investment has proven to be fairly stable. Hence, the structure of capital inflows matters for the sustainability of external financing. It depends on exogenous factors beyond the control of EMEs and economic policies pursued in EMEs whether external financing will be provided on a more sustainable basis in the future. As concerns the former, sustainable financing would be encouraged if longer-term engagements by pension funds were supported by deregulation in developed countries, and if reforms in the international financial architecture resulted in prudent bank lending. As concerns the latter, external financing requirements must be kept within reasonable limits, and capital inflows should be restructured towards relatively stable items. The timing and sequencing of capital account liberalization is crucially important to reduce the risk of a sudden reversal in capital flows. The good news for EMEs from recent capital market developments is threefold: First, EMEs are not denied access to foreign capital for long even after major economic crises. Second, in contrast to widespread belief, international capital flows are not a zero-sum game, from which only a few large and advanced EMEs can derive benefits. Third, while openness to global capital markets implies hard policy choices, it largely depends on EMEs themselves to which extent they will benefit from capital inflows.
Keywords: 330; Internationale Kapitalmobilität; Kapitalimport; Aufstrebende Märkte; Vergleich; Marktversagen; Devisenspekulation; Wirtschaftspolitik; Kapitalmarktliberalisierung; Prestige; Schwellenländer; Brasilien; Südkorea